Academic Engagement of Criminology Students in Northwestern University The Philippines - Gigi C. Abbott (Research Synergy Foundation, 2022)
Student engagement is one of the most critical methods of understanding students' behavior towards the teaching-learning process. Instructors and academic supervisors use a valuable instrument when developing successful pedagogical strategies to increase learning opportunities. This study identified the factors that influence the academic engagement of criminology students at Northwestern University. It specifically looks into the level of academic engagement as to literary identification (intellectual development and academic performance) and educational participation (number of hours spent in school activities, the extent of participation in school activities, and quality of relationship with peers, faculty, and staff), reasons for leaving the institution and the best aspects of Northwestern University to engage criminology students in learning. The study used a descriptive method using a survey questionnaire. Findings disclosed that factors under academic identification under intellectual development and academic performance often lead students from 1st to 4th year to academic engagement. The main reason for leaving the institution is personal reasons. In contrast, the best aspects of the institutions are faculty, the LMS-Canvas, academic teaching strategy, and academic materials for teaching. The research is limited only to Criminology students and covers the face-to-face learning process. The result significantly contributes to formulating instructional policies to improve students' academic engagement.